Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10899-007-9076-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Self-efficacy in Gambling: The Gambling Refusal Self-Efficacy Questionnaire

Abstract: This paper reports on the development and psychometric properties of a Gambling Refusal Self-Efficacy Questionnaire (GRSEQ). Two hundred and ninety-seven gamblers from both normal and clinical populations completed an initial set of 31-items of which 26 were selected for inclusion in the final version of the GRSEQ. A series of factor analyses showed four clear factors accounting for 84% of the variance. These factors can be summarised as situations and thoughts associated with gambling, the influence of drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 41 publications
4
69
0
1
Order By: Relevance
“…These two categories of biases were first identified among substance abusers (Oei et al 1998) and later extended to problem gamblers (Raylu and Oei 2002). Subsequent research on biases in expectancy and efficacy beliefs have also shown consistent associations with disruptive gambling among Caucasian samples (Casey et al 2008;May et al 2003;Raylu and Oei 2004a;Oei et al 2008;Steenbergh et al 2002). These findings could be explained by the social cognitive theory (Bandura 1997), which stipulates that behavior is maintained by action-outcome expectancy and efficacy beliefs specific to the context.…”
Section: Discussionmentioning
confidence: 91%
“…These two categories of biases were first identified among substance abusers (Oei et al 1998) and later extended to problem gamblers (Raylu and Oei 2002). Subsequent research on biases in expectancy and efficacy beliefs have also shown consistent associations with disruptive gambling among Caucasian samples (Casey et al 2008;May et al 2003;Raylu and Oei 2004a;Oei et al 2008;Steenbergh et al 2002). These findings could be explained by the social cognitive theory (Bandura 1997), which stipulates that behavior is maintained by action-outcome expectancy and efficacy beliefs specific to the context.…”
Section: Discussionmentioning
confidence: 91%
“…Gambling Refusal Self-Efficacy Questionnaire (GRSEQ; Casey et al 2008) is a 31-item questionnaire that assesses the respondent's level of confidence in gambling refusal using a 11-point Likert scale, ranging from zero (No confidence, cannot refuse) to 100 (Extreme confidence, certain can refuse) in four circumstances/subscales, i.e., (a) under influence of drugs (GRSEQ-DR); (b) when experiencing negative emotions (GRSEQ-NE); (c) when experiencing positive emotions (GRSEQ-PE); and (d) when in high-risk situations such as seeing others gamble (GRSEQ-ST). The total and subscale scores have shown to have high internal consistency (α from .92 to .98) as well as good criterion-related validity with SOGS (significant negative r ranging from .56 to .83).…”
Section: Gambling Related Cognitions Scale (Grcs; Raylu and Oei 2004a)mentioning
confidence: 99%
“…Gambling refusal self-efficacy refers to one's belief in resisting gambling in a particular circumstance (Casey et al 2008). Gambling refusal self-efficacy has been found to correlate negatively with gambling and PG behaviors Casey et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations